1.
f(x)=−5x−4, g(x)=6x−7, f+g
1.
f(x)=−5x−4, g(x)=6x−7, f+g
2.
g(x)=3x−5, h(x)=x+2, (h−g)(x)
2.
g(x)=3x−5, h(x)=x+2, (h−g)(x)
3.
f(x)=2x2+x−3, g(x)=x−1, f· g
3.
f(x)=2x2+x−3, g(x)=x−1, f· g
4.
f(x)=−5x+3, g(x)=6x−2, f· g
4.
f(x)=−5x+3, g(x)=6x−2, f· g
5.
f(x)=x, g(x)=x+1, fg
5.
f(x)=x, g(x)=x+1, fg
6.
f(x)=x2, g(x)=2x, fg
6.
f(x)=x2, g(x)=2x, fg
7.
f(x)=x2+x−2, g(x)=2x−4, (f+g)(x)
7.
f(x)=x2+x−2, g(x)=2x−4, (f+g)(x)
8.
f(x)=x−3, g(x)=2x−4, (f+g)(x)
8.
f(x)=x−3, g(x)=2x−4, (f+g)(x)
9.
g(x)=x−2, h(x)=3x−4, (h+g)(x)
9.
g(x)=x−2, h(x)=3x−4, (h+g)(x)
10.
f(x)=4x−8, g(x)=x−5, f+g
10.
f(x)=4x−8, g(x)=x−5, f+g